Intraoperative nerve monitoring during total shoulder arthroplasty surgery. Issue 2 (April 2014) - Malik, Atif A; Aresti, Nick; Plumb, Karen; Cowan, Joseph; Higgs, Deborah; Lambert, Simon; Falworth, Mark
Background: Nerve injury is an acknowledged complication of total shoulder arthroplasty (TSA). Although the incidence of postoperative neurological deficit has been reported to be between 1% and 16%, the true incidence of nerve damage is considered to be higher. The present study aimed to identify the rate of intraoperative nerve injury during total shoulder arthroplasty and to determine potential risk factors. Methods: A prospective study of nerve conduction in 21 patients who underwent primary or revision TSA was carried out over a 12-month period. Nerve conduction was monitored by measuring intraoperative sensory evoked potentials (SEP). A significant neurophysiological signal change was defined as either a unilateral or bilateral decrease in SEP signal of ≥50%, a latency increase of ≥10% or a change in waveform morphology, not caused by operative or anaesthetic technique. Results: Seven (33%) patients had a SEP signal change. The only significant risk factor identified for signal change was male sex (odds ratio 15.00, 95% confidence interval). The median nerve was the most affected nerve in the operated arm. All but one signal change returned to normal before completion of the operation and no patient had a persisting postoperative clinical neurological deficit. Conclusions: The incidence of intraoperative nerve damage may be more common than previously reported. However, the loss of SEP signal is reversible and does not correlate with persisting clinical neurological deficits. The median nerve appears to be most at risk. Monitoring SEPs in the operated limb during TSA may be a valuable tool during TSA.